(untitled) (Journal of Plant Disease Sciences, 2024)
This study investigates the efficacy of different Rhizobium isolates on nodulation and yield parameters of chickpea (Cicer arientinum) through field experiments conducted during the Rabi season. Field evaluations confirmed the superiority of University Rhizobium (AKCR-1) culture in promoting nodule formation and nodule fresh weight. These findings underscore the practical benefits of Rhizobium inoculation in improving chickpea productivity and soil fertility, suggesting its role in sustainable agricultural practices. Further research is recommended to optimize Rhizobium strain selection and application methods for broader agricultural adoptionand environmental benefit.